Pelatihan Pengelolaan Sampah Ramah Lingkungan Berbasis Zero Waste di SMA Nasional Makassar - Mohamad Ikbal Riski A. Danial; Amirah Mustarin; Jusran Jusran; Akmal Hidayat; Hartini Ramli (Jurnal Pengabdian Masyarakat, 2026)
The problem of plastic waste and domestic waste in the school environment is still a big challenge in creating a sustainable education ecosystem. Makassar National High School as one of the educational institutions in urban areas faces similar problems related to the high volume of daily waste. This community service activity aims to increase the awareness and skills of students and school teachers in managing waste through the application of the Zero Waste principle. The method used in this service is participatory training which includes three stages: socialization of the 5R concept (Refuse, Reduce, Reuse, Recycle, Rotting), followed by practice or simulation to deepen the understanding of the service participants. The results of the activity showed an increase in students' and teachers' understanding of the importance of environmentally friendly waste management and the ability to implement waste sorting and management practices from sources with the application of the Zero Waste principle. It is hoped that this activity can encourage changes in the behavior of students and teachers in waste management, reduce the generation of waste disposed of at the final processing site (TPA) and the creation of a school with an environmentally friendly and sustainable culture at Makassar National High School, so as to be able to reduce the burden of waste disposed of at the Final Processing Site (TPA).